2021
DOI: 10.1088/2051-672x/ac0f34
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi approach and decision tree algorithm for prediction of wear rate in zinc oxide-filled AA7075 matrix composites

Abstract: This work aims to apply data-driven approach [decision tree (DT) algorithm] to analyse the wear rate (WR) of ZnO-filled AA7075 composites. The results of model-based analysis was compared with Taguchi analysis. Stir casting was used to produce the composite samples. Characterization studies were conducted to analyse the composition and morphology. The scanning electron microscopy results indicated the even dispersion of ZnO in the AA7075. The energy-dispersive x-ray spectroscopy pattern ensures the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Based on the extensive literature review conducted, it has been understood that many factors independently affect the tribological properties of MMCs in terms of wear rate and coefficient of friction. 31 The parameters and their corresponding levels were selected from the previous studies 32 and these are shown in Table 1. Taguchi methodology is adopted to obtain the optimized parameters, which would result in the lowest wear rate and COF.…”
Section: Experiments and Methodologymentioning
confidence: 99%
“…Based on the extensive literature review conducted, it has been understood that many factors independently affect the tribological properties of MMCs in terms of wear rate and coefficient of friction. 31 The parameters and their corresponding levels were selected from the previous studies 32 and these are shown in Table 1. Taguchi methodology is adopted to obtain the optimized parameters, which would result in the lowest wear rate and COF.…”
Section: Experiments and Methodologymentioning
confidence: 99%
“…Hence, these alloys are made with self or hard ceramic particulates such as ZrO 2 [2], TiC [3], TiB 2 [4], Al 2 O 3 [5], B 4 C [6,7], ZnO [8], Si 3 N 4 [9], and Gr [10] to improve the tribological properties. The development of Al-based composites increases widespread in recent days because of it providing more wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the output of the predicted values, with original values, revealed good prediction accuracy. Balasundaram et al [22] proposed a step-by-step technique for using the decision tree algorithm to solve a twomachine flow shop scheduling problem. Ramakrishnan and Balasundaram [8] applied regression models to the boronizing process of SS310.…”
Section: Literature Surveymentioning
confidence: 99%